A New Signaling Pathway for HCV Inhibition by Estrogen: GPR30 Activation Leads to Cleavage of Occludin by MMP-9 - Ulitzky, Laura; Lafer, Manuel M.; KuKuruga, Mark A.; Silberstein, Erica; Cehan, Nicoleta; Taylor, Deborah R. (PLOS ONE, 2016)
Poor outcome in response to hepatitis C virus, including higher viral load, hepatocellular carcinoma and cirrhosis, is more associated with men and postmenopausal women than with premenopausal women and women receiving hormone replacement therapy, suggesting that β-estradiol plays an innate role in preventing viral infection and liver disease. Consequently, most research in the field has concluded that estrogen affects HCV replication through viral interactions with estrogen receptor-α. Previously, estrogen-like antagonists, including Tamoxifen, were shown to reduce HCV RNA production and prevent viral entry, although the authors did not identify host factors involved. Estrogen can act alternatively through the membrane-bound G-protein-coupled estrogen receptor, GPR30. Here, human hepatoma Huh7.5 cells were infected with HCV J6/JFH-1 and treated with estrogen or Tamoxifen, resulting in a marked decrease in detectable virus. The effect was mimicked by G1, a GPR30-specific agonist, and was reversed by the GPR30-specific antagonist, G15. While previous studies have demonstrated that estrogen down-regulated occludin in cervical cancer cells, its action on liver cells was unknown. Occludin is a tight junction protein and HCV receptor and here we report that activation and cellular export of MMP-9 led to the cleavage of occludin upon estrogen treatment of liver cells. This is the first report of the cleavage of an HCV receptor in response to estrogen. We also identify the occludin cleavage site in extracellular Domain D; the motif required for HCV entry and spread. This pathway gives new insight into a novel innate antiviral pathway and the suboptimal environment that estrogen provides for the proliferation of the virus. It may also explain the disparate host-virus responses to HCV demonstrated by the two sexes. Moreover, these data suggest that hormone replacement therapy may have beneficial antiviral enhancement properties for HCV-infected postmenopausal women and show promise for new antiviral treatments for both men and women.